Effect of Piperonyl Butoxide and Silver Nitrate on Degradation Pathways of n-octadecane by Fusarium sp. F092 - Hidayat, Asep; Tachibana, Sanro (Indonesian Journal of Forestry Research, 2016)
The aliphatic fraction is usually the largest component in crude oil. Its removal from oil contaminated fields has become an environmental priority and been considered useful for enhancing recovery. Our previous studies reported the isolation of Fusarium sp. F092 based on the ability to degrade chrysene. It also could degrade crude oils and their aliphatics fractions. However, aliphatic degradative pathways in crude oil have not been clearly understood. The identification of aliphatic metabolite pathways using a representative compound n-octadecane was carried out in this study, as well as the effect of Piperonyl Butoxide (PB) and Silver Nitrate (AgNO3) on the degradation of n-octadecane and its metabolite. We determined that Fusarium sp. F092 had ability to break down n-Octadecane from about 125 to 13 mg L-1 after 60 days incubation. During degradation, several metabolite products could be detected and identified to form carboxylic acid groups. By the addition of PB and AgNO3, inhibitor of monooxgenase and dioxygenase enzymes, Fusarium sp. F092 had ability to convert n-octadecane to form alkyl hydroperoxides via terminal oxidation pathway with involving a dioxygenase